The Problem of State Jurisdiction in the Judicial Authority Law of the Kurdistan Region - Piru, Baida Saleh (Journal of Legal and Political Studies, 2016)
State level jurisdiction is considered one of the most important types of jurisdiction where judicial jurisdiction is distributed on its basis between the various judicial bodies within a single country. The reason behind that is the difficulty of the jurisdiction on concentrating in one direction.This principle has become one of the principles of the judicial system in the contemporary states because jurisdiction is one of the basic functions of the state and usually this jurisdiction is determined by legal clauses.The Article 5 of the Judicial Authority Law of the Kurdistan Region No. 23 of the year 2007, which shows the authority of the courts in the Kurdistan Region, mentions this principle but does not mention the phrase (except those exempted by a special provision) which came in the provisions of the Civil Procedure Law and the Law on Judicial Organization in Iraq.This has resulted in differences in the positions of the Kurdistan courts in this field and was the reason for the issuance of contradictory judgments.This research sheds light on this problem and tries to find a solution to show the right direction among the positions of the Kurdistan courts.
Keywords: judicial jurisdiction; Judicial Authority Law of the Kurdistan Region; Civil Procedure Law; positions of the Kurdistan courts